2007
DOI: 10.1116/1.2737439
|View full text |Cite
|
Sign up to set email alerts
|

Low bias reactive ion etching of GaAs with a SiCl4∕N2∕O2 time-multiplexed process

Abstract: An inductively coupled plasma reactive ion etching process was developed for transferring patterns from a thin intermediate mask consisting of Ni or SiNx into GaAs. Smoothed out etch floors and sidewalls can be achieved under an approximately 200V bias by switching between an anisotropic etch phase and a deposition phase by gas chopping. The deposition of Si–O based film that protects the sidewall from chlorine attack is promoted by the addition of O2 to an SiCl4∕N2 gas mixture. The total achieved etch depth w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…However there has been limited success as we were unable to find any relevant research in the literature. In 2007, Golka et al [11] published nice results on the directional pulsed-mode DRIE though it was limited to GaAs etching at relatively low speed. The deposition of SiO x -based film was promoted by the mixing of O 2 with SiCl 4 gas during the deposition step, as found earlier by Varoutsis et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…However there has been limited success as we were unable to find any relevant research in the literature. In 2007, Golka et al [11] published nice results on the directional pulsed-mode DRIE though it was limited to GaAs etching at relatively low speed. The deposition of SiO x -based film was promoted by the mixing of O 2 with SiCl 4 gas during the deposition step, as found earlier by Varoutsis et al [12].…”
Section: Introductionmentioning
confidence: 99%
“…The anisotropic etching of III-V materials in SiCl 4 chemistries has been already reported in the literature. [7][8][9] In this work we show that etched features with a vertical and smooth profile can be obtained using SiCl 4 /H 2 gas mixture without the assistance of the C-Si electrode coverplate, and we discuss the importance of the simultaneous presence of Si and H species in the plasma. We then investigate the possibility of adding SiH 4 , containing both Si and H species, in order to obtain anisotropic InP etching independently of the electrode coverplate material.…”
Section: Introductionmentioning
confidence: 78%
“…7,9 We have also shown that, under our plasma conditions, smooth and anisotropic ICP etching could not be obtained if the Si wafer was re-placed by another material ͑e.g., Al 2 O 3 , AlN, or SiO 2 wafers͒. 11 SiCl 4 has also been successfully used for the ICP etching of InP. or more and used to etch III-V samples of smaller size ͑2 in.…”
Section: Introductionmentioning
confidence: 99%